Porno Aksi dalam Pertunjukan Musik pada Masyarakat Pedesaan: Kasus Elekton Candoleng-Doleng di Kabupaten Sidrap - Muhammad Al Ihzan (Rayhan Intermedia, 2018)
This study aims to determine the origin of the emergence of Candoleng-doleng in Sidrap, public opinion about Candoleng-doleng and the impact of the existence of Candoleng-doleng. This research is a descriptive qualitative research, which produces descriptive data in the form of written or oral words from the behavior of the people observed. Researchers observed and interacted with community leaders, prominent figures, and youth leaders in Bulucenrana Village using observation, interview and documentation methods. Based on the results of research, it is known that the show or the type of musical entertainment elekton Candoleng-doleng began to be known and developed in Sidrap district around 2008, and in an instant, the erotic shake that became very popular among the people, this is because the action of candoleng-doleng appear cheap. For those who love music entertainment elekton Candoleng-doleng they cannot be separated from their hobby, candoleng-doleng has become a magnet for those who are always present in every elekton Candoleng-doleng musical performances. While the music lovers community of elekton Candoleng-doleng did not consider this show as an action that leads to pornoaction, because they assume that what it does is not harmful to others, in fact what actually happens is a kind of justification, the audience gets satisfaction on the action being shown by elekton's singing, while the singer receives the money from his performance.